STATUS SOSIAL EKONOMI TERHADAP UTILISASI DAN OUT OF POCKET PESERTA ASURANSI KESEHATAN (ANALISIS DATA INDONESIAN FAMILY LIFE SURVEY 2007 DAN 2014) - Endra Dwi Mulyanto; Julita Hendrartini; Firdaus Hafidz As Shidieq (Journal of Health Service Management, 2020)
Background: The government has guaranteed equal rights for each individual to access health services. It is mandated in the Law Number 40 of 2004 on National Social Security System (SJSN) which emphasizing social insurance program. The social insurance is expected to improve the access and utilization of health services and to minimize the risk of out of pocket. Objective: To provide empirical evidence related to the impact of health insurance ownership toward the outpatient utilization and out of pocket based on socioeconomic status. It also examines the factors influencing outpatient utilization and out of pocket. Methods: The study used 2007 and 2014 Indonesian Family Life Survey (IFLS) data. The representative data were collected from individuals aged more than 15 years in 13 provinces in Indonesia through questionnaire with cross-sectional design. The data were analyzed step by step covering univariable, bivariable, and multivariable through Fixed Effect Model (FE). Results: The outpatient utilization indicated that: 1) The socioeconomic status influences the level of outpatient visit, specifically quantile 2 (OR=1,6), quantile 4 (OR=2,0), and quantile 5 (OR=1,8); 2) The outpatient utilization reached OR=1,8 for individual aged ≥60 years; 3) OR=3,6 for individuals completing junior high school and above; 4) OR= 2,7 for individual who was sick in the past one week; 5) OR= 1,4 for married individuals; and 6) OR= 1,9 for individuals suffering from heart disease. However, the individuals with socioeconomic status in quantile 4 spent higher Out of Pocket (54%); individuals in quartile 5 spent 46%; and individual with hypertension spent 48%. Conclusion: Changes in socioeconomic status affect the increase in outpatient utilization and out of pocket cost. In addition to socioeconomic status, outpatient utilization and out of pocket are affected by hypertension.